Ionic liquids for keratin fibre modification - Trindade, Margarida (2022)
The human hair has been wasted in many parts of the world and even considered useless, however human hair is a great source of keratin. Keratin represents an important renewable biomaterial which could be further explored. The number of applications is vast and due to its potential, the dissolution of human hair was further investigated in this Thesis.